Student’s Interest-Based Identifying Industry Preference Strategy as A Means of English Literature Study Program Support for Independent Learning - Independent Campus Program - Fatma Hetami; Mohamad Ikhwan Rosyidi; Izzati Gemi Seinsiani; Thohiriyah Thohiriyah (Universitas Negeri Semarang, 2021)
This research is conducted by concerns about the gap in the competence of graduates with the demands of the industrial world. On the one hand, the industrial world often complains about the competencies of university graduates which are often not in line with expectations, while on the other hand students often do not understand what competencies they should have so that they are in line with industry expectations. In this regard, this research was conducted to strengthen the capacity of universities, especially the UNNES English Literature Study Program to support the Independent Learning - Independent Campus Program (Merdeka Belajar-Kampus Merdeka-MBKM) in terms of internships through the strategy of identifying industrial preferences based on student interests. The objectives of this study are (1) to explain the link and match relationship between study programs and industry, (2) to develop a collaborative design system for study programs and industry, (3) to develop strategies for achieving innovative internship designs that are in line with the needs of students and industry. This study used Research and Development (R&D) method. The instrument used was a questionnaire. The data collection technique was done by giving a questionnaire to the research participants. Researchers distributed questionnaires for students to gain data on student preferences/interests in choosing internship locations, as well as distributing questionnaires for industries that were included in the list of student preferences. In addition, researchers conducted forum group discussion (FGD) to identify the competencies of graduates expected by the industry. This study involved 108 undergraduate students of the 2019 and 2018 batch in the English Literature Study Program at Universitas Negeri Semarang and 21 respondents from industrial world business (DUDI-Dunia Usaha Dunia Industri) partners that become the student internship preferences. The results of this study indicate that there is a data mapping of 4 major fields of work that are student preferences, namely tourism, offices, translation, and journalism. The prototype for the collaborative design of industrial and study program is achieved through several activities, including FGD that has been carried out, the internship fair and internship corner which will be implemented next year. Meanwhile, the strategy for achieving innovative internship designs is achieved in two ways, namely the creation of an Independent Learning-Independent Campus-based guide book and a partner profile book.